Fabrication of 3-dimensional cross-linked redox enzyme/nanomaterials - A. K. M., Kafi; Nina Suhaity, Azmi; Mashitah, Mohd Yusoff; Crossley, Maxwell J. (Elsevier Ltd, 2017)
A grand challenge for the scientific community in the rapidly progressing field of biosensors and bioelectronics is the coupling of biomolecules with electronics to achieve high current outputs at low concentration of substrates, thus leading to highly sensitive biosensors and ultimately enabling their applicability for real applications in complex matrices, e.g. biological residue, environmental samples, etc. Communication between the biological and non-living worlds is effected by the passage of electrons and designing appropriate interfaces to facilitate this has been extremely difficult to achieve to date.